2003
DOI: 10.1179/016164103101202002
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular risk factors in Alzheimer's disease: Brain hemodynamics and pharmacogenomic implications

Abstract: Recent evidence indicates that different vascular risk factors are present in Alzheimer's disease (AD) and other prevalent dementia types probably contributing to deterioration of cerebrovascular function, thus enhancing neurodegeneration and premature neuronal death due to a reduction in brain perfusion. Brain blood flow shows a reduced velocity and increased pulsatility (PI) and resistance indices (RI) in different types of dementia and in diabetes and hypertension, as well. High levels of diastolic blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…These risk factors appear to be exacerbated in individuals carrying the apolipoprotein E4 (APOE ε4) allele such that they have an increased risk of developing type -2 diabetes, hypertension, hypercholesterolaemia, cardiovascular disease and Alzheimer's disease (reviewed in [6,42]). This increase risk in APOE ε4 carriers maybe partly attributed to diet.…”
Section: Introductionmentioning
confidence: 99%
“…These risk factors appear to be exacerbated in individuals carrying the apolipoprotein E4 (APOE ε4) allele such that they have an increased risk of developing type -2 diabetes, hypertension, hypercholesterolaemia, cardiovascular disease and Alzheimer's disease (reviewed in [6,42]). This increase risk in APOE ε4 carriers maybe partly attributed to diet.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral sources of Aβ peptides, cholesterol and inflammatory lipids, by transversing a damaged or leaky blood brain barrier, may further contribute to Aβ deposition in the AD brain (Aliev et al, 2003;Chaney et al, 2003). Due to a reduction in brain perfusion and altered hemodynamic properties, damaged, diseased, or dysfunctional cerebral vasculature may promote premature neuronal death as observed in multiple infarct dementia, in cerebral vascular dementia and in AD brain (Cacabelos et al, 2003;Aliev et al, 2003;Ravona-Springer et al, 2003;Fitzpatrick et al, 2004).…”
Section: Cardiovascular Disease Cholesterol and Admentioning
confidence: 96%
“…It has been suggested that differences in the clinical observations in AD and VaD patients may be due to the type, severity and location of vascular damage [133][134][135]. Furthermore, perturbations in vascular hemodynamics have been observed in VaD and AD [136,137], however, AD patients had comparatively less impairment in cerebral perfusion than those with VaD [138] suggesting that hemodynamic disturbances may underlie different types of dementia [138]. While the precise mechanism that vascular risk factors initiate cognitive decline remains elusive [139], T2DM have been identified as an important contributing factor to the development of VaD.…”
Section: Vascular Dementia Versus Alzheimer's Dementiamentioning
confidence: 99%